Toward a National Initiative in Cancer Rehabilitation: Recommendations From a Subject Matter Expert Group - Stout, Nicole L; Silver, Julie K; Raj, Vishwa S; Rowland, Julia; Gerber, Lynn; Cheville, Andrea; Ness, Kirsten K; Radomski, Mary; Nitkin, Ralph; Stubblefield, Michael D; Morris, G Stephen; Acevedo, Ana; et al. (Archives of physical medicine and rehabilitation, 2016)
The health care delivery system in the United States is challenged to meet the needs of a growing population of cancer survivors. A pressing need is to optimize overall function and reduce disability in these individuals. Functional impairments and disability affect most patients during and after disease treatment. Rehabilitation health care providers can diagnose and treat patients' physical, psychological, and cognitive impairments in an effort to maintain or restore function, reduce symptom burden, maximize independence and improve quality of life in this medically complex population. However, few care delivery models integrate comprehensive cancer rehabilitation services into the oncology care continuum. The Rehabilitation Medicine Department of the Clinical Center at the National Institutes of Health with support from the National Cancer Institute and the National Center for Medical Rehabilitation Research convened a subject matter expert group to review current literature and practice patterns, identify opportunities and gaps regarding cancer rehabilitation and its support of oncology care, and make recommendations for future efforts that promote quality cancer rehabilitation care. The recommendations suggest stronger efforts toward integrating cancer rehabilitation care models into oncology care from the point of diagnosis, incorporating evidence-based rehabilitation clinical assessment tools, and including rehabilitation professionals in shared decision-making in order to provide comprehensive cancer care and maximize the functional capabilities of cancer survivors. These recommendations aim to enable future collaborations among a variety of stakeholders to improve the delivery of high-quality cancer care.